Jumping the welfare gap in designing public transfers - András Simonovits (Hungarian Academy of Sciences, Institute of Economics, 2017)
We consider three transfer models with a representative individual who discounts the utility of the merit good with respect to the standard one's. In each model, a paternalistic government taxes the consumer and transfers him additional merit goods in return. The private purchase of the merit goods is cheaper than the transfer. Even if the optimal transfer system is welfare superior to the transfer-free system, a system with much lower transfer may be inferior, therefore this welfare gap should be jumped. Various pension modelers (e.g. Feldstein, 1985; van Groezen, Leers and Meijdam, 2003) overlooked this problem and drew wrong conclusions.
Keywords: D10; H55; J13; J14; J18; J26; 330; transfers; pensions; taxes; social welfare; paternalism